A combined ultrasound + membrane ultrafiltration (USN-UF) process for enhancing saccharides separation from Spirulina (Arthrospira platensis). (May 2023) - Zhou, Jianjun; Wang, Min; Barba, Francisco J.; Zhu, Zhenzhou; Grimi, Nabil
Abstract: In this study the combination of ultrasound (USN) + membrane ultrafiltration (UF) was used to separate Spirulina saccharides (SPS). The results showed that USN significantly ( p  < 0.05) increased the average high-added-value compounds yield (mainly protein 572.8 mg/g, saccharides 133.6 mg/g and polyphenols 33.6 mg/g, dw) when the setting of 400 W/10 min was applied. Scanning electron microscope (SEM) results showed that USN treatment effectively destroyed Spirulina microstructure. The extraction efficiency differed according to USN total energy consumption, with higher extraction efficiency observed when a cooling system was not used. Different molecular weight cut-offs (MWCOs) membranes were used to separate SPS. Relative high purity SPS (∼70%) were obtained when 4 and 10 kDa membranes were used, while a higher separation efficiency occurred when using 100 and 150 kDa membranes. USN treatment increased the concentration of relatively low molecular weight SPS (4, 10 kDa) in the permeate ( p  < 0.05) but there was no significant ( p  > 0.05) effect on the high molecular weight SPS (300, 500 kDa). Membrane fouling was observed during the saccharides UF process, thus indicating that the process could be further improved. Highlights: Ultrasonic extraction of algae nutrients without cooling system saves energy Ultrasonic effect greatly destroys the microscopic morphology of Spirulina Ultrasonic extraction enhances membrane ultrafiltration of saccharides Membrane fouling in ultrafiltration process is related to membrane pore size